2016
DOI: 10.1089/ars.2016.6747
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on Reactive Oxygen Species Detection—Learning from the Phagosome

Abstract: Difficulties due to cell movement and continuous formation of new phagosomes can be reduced by ratio measurements, if appropriate dyes are identified. For detection in live cells and subcellular locations, fluorescent proteins (FPs) offer several advantages and are used to create biosensors for ROS. Some FPs are directly sensitive to certain ROS as shown here. Although this may compromise their use in an environment with high levels of ROS, it can also be exploited for ROS measurement directly with the FPs the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 84 publications
(98 reference statements)
0
24
0
Order By: Relevance
“…Figure 4D shows the statistical analyses (charge, Q, Figure 4D1; current maximum, I max ,F igure 4D2, and halflife, t 1/2 ,F igure 4D3) of 427 current spikes recorded from 5 different macrophages.T he corresponding distributions establish that the amount of ROS/RNS released by each ruptured phagolysosome was highly variable and followed log-normal distributions (Supporting Information, Figure S8) presumably reflecting the rather large variations achieved during their maturation. [14,17] Nonetheless,b ased on Faraday law, [18] the median charge of circa 10 fC indicated that the average phagolysosome contained between 31 250 and 62 500 ROS/RNS molecules. [18b] In conclusion, this work presented an easy and highly reproducible strategy for fabricating high-performance nanowire electrodes with unique abilities for intracellular electrochemical detection.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4D shows the statistical analyses (charge, Q, Figure 4D1; current maximum, I max ,F igure 4D2, and halflife, t 1/2 ,F igure 4D3) of 427 current spikes recorded from 5 different macrophages.T he corresponding distributions establish that the amount of ROS/RNS released by each ruptured phagolysosome was highly variable and followed log-normal distributions (Supporting Information, Figure S8) presumably reflecting the rather large variations achieved during their maturation. [14,17] Nonetheless,b ased on Faraday law, [18] the median charge of circa 10 fC indicated that the average phagolysosome contained between 31 250 and 62 500 ROS/RNS molecules. [18b] In conclusion, this work presented an easy and highly reproducible strategy for fabricating high-performance nanowire electrodes with unique abilities for intracellular electrochemical detection.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Similarly,n oc urrent spikes could be observed when the same experiments were performed inside Hela cells that do not contain ROS/RNS-loaded vesicles (Supporting Information, Figure S7 A), or upon inserting non-platinized SiC@C NWEs into RAW2 64.7 macrophages (Figure S7 B). [14,17] Nonetheless,b ased on Faraday law, [18] the median charge of circa 10 fC indicated that the average phagolysosome contained between 31 250 and 62 500 ROS/RNS molecules. Figure 4D shows the statistical analyses (charge, Q, Figure 4D1; current maximum, I max ,F igure 4D2, and halflife, t 1/2 ,F igure 4D3) of 427 current spikes recorded from 5 different macrophages.T he corresponding distributions establish that the amount of ROS/RNS released by each ruptured phagolysosome was highly variable and followed log-normal distributions (Supporting Information, Figure S8) presumably reflecting the rather large variations achieved during their maturation.…”
mentioning
confidence: 99%
“…They also revealed that the probe may become completely oxidized in the phagosome and the fluorescence measurement reaches a plateau due to probe saturation, not due to the actual end of ROS production. Optimizing the quantity of dye on each particle extended (107).…”
Section: R672mentioning
confidence: 99%
“…Changes in intraphagosomal pH; salt concentrations; digestive enzymes, notably proteases; and a wide range of different ROS at varying concentrations need to be taken into account. Although the phagosome appears as an extreme case of harsh environment, other physiological and pathological settings such as the mammalian digestive tract may impose similar chemical conditions (107). There is a need for new synthetic probes for those conditions.…”
Section: R672mentioning
confidence: 99%
See 1 more Smart Citation